Developing an Alternative Measurement of Corporate Reputation within the Malaysian Context - Dwi Sunu Kanto, Slamet Widodo; Ernest Cyril, de Run; Abu Hassan, Md. Isa (Institute of Interdisciplinary Business Research, 2013)
The measurement of corporate reputation is a growing issue for practitioners and academics. The corporate reputation measurement literature concentrates on the United States and European countries. There is an obvious lack of studies especially on the development of corporate reputation measurement in Malaysia. While interest in the development of corporate reputation measurement has gained momentum in the last thirteen years, a precise commonly agreed upon the measurement is still unclear. Therefore, this paper set out to develop a conceptual model for developing an alternative measurement of corporate reputation within the Malaysian context. Literature review, conceptual model, hypotheses development and research methodology are discussed. These will allow companies in Malaysia to develop a new measurement of corporate reputation.